PHENOTYPIC TRAITS AND CHEMICAL PROPERTIES OF JATROPHA CURCAS SEEDS FROM NORTHERN GHANA - Hellie Gonu; Nelson Opoku; Regina Appiah-Opong; Kugbe Joseph; Michael Teye Barnor; Philip Quarm (European Scientific Journal, ESJ, 2015)
This study was carried out to examine the physical features, proximate composition and oil quality of Jatropha curcas seeds from Nyankpala and Bole in the Northern Region of Ghana. The unit mass of J. curcas seed and kernel, length, width, breadth, geometric and arithmetic mean diameter, volume, bulk density, solid density and sphericity were considered. The physical properties of J. curcas seed and kernel between the two provinces were significantly different (p ≤ 0.05) with the exception of bulk density. The geometric features of seeds and kernel from Nyankapla were greater than those from Bole. Proximate composition of crude protein for Nyankpala and Bole was 21.67 ± 0.795 and 23.14 ± 0.781 respectively. Ether extract of J. curcas seeds from Bole (22.41± 2.98%) was significantly higher (p<0.05) than from Nyankapla (18.37± 2.14). Oil properties indicated stability and high saturation among the oil samples. The study reveals that variation in agro-climatic conditions of the two provinces influence the seed physical features. This finding will serve as useful data for the design and improvement of J. curcas seed and kernel processing machine and for the use of J. curcas seed meal as potential feed in animal husbandry.